Entry mode choice of Singapore software firms into the International/Regional markets. - Chung, Susan Lai Ling. (2009)
At a regionalization forum in June 1993, Singapore's Prime Minister, Mr Goh Chok Tong , commented that the local economy has matured to a stage where it needs to add an external dimension to supplement the domestic economy. He believed that this move can help the local economy as well as local businesses grow stronger and bigger. In fact, at the business level, these macro objectives are fortified by a stronger pressure - the need to remain competitive. Many businesses are actually venturing overseas out of strategic necessity.